Using STATCOM with Energy Storage to Enhance the Stability of AC-DC Hybrid System - Zheng Xu; Ding Jianyong; Li Mei; Zhao Shuang; Zeng Ni; Zhu Ruoxi; Zhang Buhan; Mao Chengxiong (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
UHVDC has been rapidly developed for its large conveying capacity, small net loss and easy power control, which can solve the problem of the uneven distribution of load and energy with great economy. However, with DC transmission access, the power system must have a strong ability of reactive power support to cope with the possibility of transient voltage problem. At the same time, regional power oscillation issue also can’t be ignored. Considering that the STATCOM device, as a type of parallel FACTS, can only provide dynamic reactive power to support the system voltage and cannot undertake active regulation and control to damp system power oscillation problem, STATCOM with energy storage is presented in this paper to solve both problem of transient voltage and power oscillation in AC-DC hybrid system. In view of the central China province power grid planning, possible serious faults of the system were analyzed. The simulation results show that STATCOM with energy storage cannot only effectively support the system transient voltage and promote voltage of dc inverter station to avoid DC block caused by commutation failure, but also can significantly enhance the system damping and restrain regional power oscillation in case of system failure.